The Role of Collective Action Frame in Women’s Recruitment in Meterbyaj Aandolan of Nepal - Adhikari, Kalpana (NPRC Journal of Multidisciplinary Research, 2026)
Background: The Meterbyaj Aandolan (MBA) is a grassroots movement against predatory lending in Nepal that witnessed unprecedented participation of marginalized women. However, past social movement studies in Nepal have rarely examined how framing processes specifically enable women’s recruitment in financial grassroots movement.Methods: This study employed a qualitative descriptive design grounded in interpretivism. Semi-structured interviews were conducted with twelve movement members (four main leaders, four women local leaders, and four cadres) between August-October 2025. Fifteen days of field observation (January 2025) and analysis of movement documents, government reports, and news articles supplemented the interviews. Data were analyzed using inductive thematic analysis (Braun & Clarke, 2006).Results: The MBA used diagnostic framing and its resonance frame to recruit women. Through sub-frame problem identification and attribution, identify meterbyaj as structural injustice rather than individual failure, attributing blame to moneylenders, complicit officials, and weak financial laws. This frame was intensified through gendered reframing of victimhood, converting women’s isolated experiences (double household burden, harassment, and stigma) into public gender injustice. Frame resonance was achieved through cultural resonance and local narratives cultural expressions (Maithili/Bhojpuri language, regional dress, local movement institutions). Additionally, collective identity and empowerment messaging frame deploying the commanding trainings, leadership responsibilities, and identity formation work proved crucial for recruiting and sustaining long-term participation.Conclusion: Women’s mass participation in the MBA was not spontaneous but deliberately through culturally rooted, gender-sensitive, and emotionally resonant framing practices that converted humiliation into agency and suffering into collective action.Novelty: This study is the first to apply collective action framing theory to a financial grassroots movement in Nepal, demonstrating that strategic framing particularly diagnostic and its resonance frames are fundamental to recruiting and sustaining women’s participation.